Using contribution analysis to evaluate health professions and health sciences programs - Choi, Tammie; Sarkar, Mahbub; Bonham, Maxine; Brock, Tina; Brooks, Ingrid Ann; Diug, Basia; Ilic, Dragan; Kumar, Arunaz; Lau, Wee-Ming; Lindley, Jennifer; Morphet, Julia; Simmons, Margaret; et al. (Frontiers in Medicine, 2023)
Course evaluation in health education is a common practice yet few comprehensive evaluations of health education exist that measure the impacts and outcomes these programs have on developing health graduate capabilities.Aim/objectives: To explore how curricula contribute to health graduate capabilities and what factors contribute to the development of these capabilities.Methods: Using contribution analysis evaluation, a six-step iterative process, key stakeholders in the six selected courses were engaged in an iterative theory-driven evaluation. The researchers collectively developed a postulated theory-of-change. Then evidence from existing relevant documents were extracted using documentary analysis. Collated findings were presented to academic staff, industry representatives and graduates, where additional data was sought through focus group discussions -one for each discipline. The focus group data were used to validate the theory-of-change. Data analysis was conducted iteratively, refining the theory of change from one course to the next.Results: The complexity in teaching and learning, contributed by human, organisational and curriculum factors was highlighted. Advances in knowledge, skills, attitudes and graduate capabilities are non-linear and integrated into curriculum. Work integrated learning significantly contributes to knowledge consolidation and forming professional identities for health professional courses. Workplace culture and educators' passion impact on the quality of teaching and learning yet are rarely considered as evidence of impact.Discussion: Capturing the episodic and contextual learning moments is important to describe success and for reflection for improvement. Evidence of impact of elements of courses on future graduate capabilities was limited with the focus of evaluation data on satisfaction.Conclusions: Contribution analysis may behas been a useful evaluation method to explore the complexity of the factors in learning and teaching that influence graduate capabilities in health-related courses.